PRAKTIK DIGITALPRENEUR INDUSTRI 4.0 (Studi Kasus Digitalpreneur Mahasiswa Universitas Trunojoyo Madura Perspektif Pierre Bourdieu) - Hamzah Fansuri; Hisnuddin Lubis (Hermeneutika : Jurnal Hermeneutika, 2020)
PRAKTIK DIGITALPRENEUR INDUSTRI 4.0 (Studi Kasus Digitalpreneur Mahasiswa Universitas Trunojoyo Madura Perspektif Pierre Bourdieu)Moh. Hamzah Fansuri¹, Hisnuddin Lubis² Program Studi Sosiologi, Jurusan Ilmu Sosial dan Ilmu Budaya, Fakultas Ilmu Sosial dan Ilmu Budaya, Universitas Trunojoyo Madura E-mail: hamzahfansuri268@gmail.com    Abstract - Digitalpreneur is one form of an entrepreneur business through an internet network, the network is used by various groups as a place to sell/buy products (goods/services) based online. In this study, the focus of digitalpreneur among the students of University of Trunojoyo Madura, where this business model is classified as easy to run from the perspective of (e-marketing), payment transactions (e-money/virtual) and shipping without having to meet directly with consumers.The purpose of this study is to find out the opportunities of Digitalpreneur for students of University of Trunojoyo Madura in facing the challenges of Industry 4.0 Pierre Bourdieu's perspective by looking at new practices born in the process which able to change the hobby of community (traditional society) in shopping, noticeable changes in patterns think online shopping especially for millennial generations.The method used is qualitative with data collection methods using observation, interviews, and documentation. Informants in this study are selected using purposive sampling. The analysis used by using Miles and Huberman analysis techniques. while in checking the validity of the data using the source triangulation method.Keywords: Digitalpreneur, Pierre Bourdieu, Industry 4.0